ON MULTIPLICATION OF HALL-LITTLEWOOD FUNCTIONS - Sultana, N. (Journal of Research (Science), 2001)
The subject of investigation in this paper is the multiplication of Hall-Littlewood symmetric functions. The main tool is to find the particular formula forthe coefficient υλ ,(r 1,r ) f − (t) in the product of two HL-functions.